2006
DOI: 10.1002/cncr.21703
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of patients with fibrolamellar hepatocellular carcinoma

Abstract: BACKGROUNDFibrolamellar hepatocellular carcinoma (FL‐HCC) is a rare variant of hepatocellular carcinoma, has distinct pathologic features, and typically occurs in young patients without underlying hepatitis or cirrhosis.METHODSForty‐one patients with the pathologic diagnosis of FL‐HCC evaluated at our institution between 1986 and 2003 were identified from a prospective database.RESULTSMedian age of all patients was 27 years. None of these patients had underlying hepatitis or cirrhosis, and only 3 (7%) patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
215
2
18

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(244 citation statements)
references
References 23 publications
9
215
2
18
Order By: Relevance
“…However, this latter finding is controversial. [18][19][20] A recent study of 95 patients from the Fibrolamellar Carcinoma Consortium reported a median survival of 6.7 years, 2 and based on data from SEER 18 registries from 2000 to 2010 the overall 5-year survival was significantly better among fibrolamellar carcinoma patients (34%) compared with other patients with hepatocellular carcinoma (16%). 20 However, in patients who have received a potentially curative form of treatment (resection, transplantation, or radiofrequency ablation), there was no difference in survival between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, this latter finding is controversial. [18][19][20] A recent study of 95 patients from the Fibrolamellar Carcinoma Consortium reported a median survival of 6.7 years, 2 and based on data from SEER 18 registries from 2000 to 2010 the overall 5-year survival was significantly better among fibrolamellar carcinoma patients (34%) compared with other patients with hepatocellular carcinoma (16%). 20 However, in patients who have received a potentially curative form of treatment (resection, transplantation, or radiofrequency ablation), there was no difference in survival between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Separate Note on FL-HCC [43][44][45][46][47][48][49][50] Because the analysis of the literature shows that NC-HCC and FL-HCC are still perceived differently on account of their different clinical presentations, courses, imaging results, and outcomes, some brief remarks about this tumor variant are made here.…”
Section: Resultsmentioning
confidence: 99%
“…Tumor recurrence can occur late, even after 5 or 10 years, and repeat hepatectomy (reported in 20%-60% of patients) can significantly prolong survival. 45,48 Vascular involvement and lymph node involvement are significant prognostic factors, but the tumor number, the tumor size, and the use of chemotherapy are not. 48 The somewhat better results reported after hepatectomy versus LT can be explained by the more advanced tumor stages and immunosuppression in liver recipients, as shown in the transplant series from Hannover (8 patients), 48 Birmingham, UK (9 patients), 44 and Pittsburgh (13 patients).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Se presenta fundamentalmente en adolescentes y adultos jóvenes como una masa tumoral hepática única, frecuentemente de gran tamaño, no asociada a cirrosis y rodeada de una cápsula fibrosa. Su diseminación es preferentemente a través de metástasis linfáticas regionales 2,3 . En nuestro país sólo se han comunicado casos aislados 4 .…”
Section: Fibrolamellar Hepatocellular Carcinoma (Flc) Is a Rare Histounclassified